Wilt-based irrigation in Kentucky bluegrass: effects on visual quality and irrigation amounts among cultivars - Lewis, Jason D.; Bremer, Dale J.; Keeley, Steven J.; Fry, Jack D. (My University, 2012)
A critical challenge facing the turf industry is increasingly limited water supplies. Identifying cultivars that use less water while maintaining acceptable quality may mitigate irrigation demands. Our objectives were to identify Kentucky bluegrass (Poa pratensis L.) (KBG) cultivars and phenotypic groups that maintained better visual quality with less water. Thirty bluegrass selections were evaluated in a 2-yr field study under a rainout shelter near Manhattan, KS. Irrigation (2.5 cm) was applied when >50% of a plot exhibited visible wilt symptoms. Visual quality was rated daily. Average irrigation applications ranged widely from 23.3 cm (mean = 2.2 mm d[superscript]−1) in Bedazzled to 44.9 cm (mean = 4.2 mm d[superscript]−1) in Kenblue, and days to wilt between irrigations ranged from 6.4 d in Kenblue to 13.1 d in Cabernet. Visual quality averaged at or slightly below 6.0, defined as “minimally acceptable,” but this may be adequate when water conservation is a priority and some dormancy is tolerable; irrigation at <50% wilt is recommended for improved quality. Based on statistical range tests, 15 of the 30 cultivars were grouped as both receiving the least water and having the greatest visual quality. Overall, the Compact America and Mid-Atlantic KBG groups exhibited the greatest days to wilt and received the least water. Results suggest that Compact America and Mid-Atlantic phenotypes have the greatest potential for integrating reduced water inputs with maintenance of acceptable visual quality.
Keywords: Wilt-based irrigation; Kentucky bluegrass; Visual quality; Turf management